Sustainable production of afforestation and reforestation to salvage land degradation in Asunafo District, Ghana - Kenneth Peprah (Brawijaya University, 2017)
Savannazation and marshy areas are common features of once evergreen and deciduous forest of Ghana. Attempts to salvage such degraded lands have considered replacement with closed tree canopy. This study aims at examining efforts at Asunafo forest area to use tree planting of different species to remedy land degradation in a swamp area colonized by shrubs and grasses. Study methods include the use of field visits and transect walk, photography, archival data, key informant interview, community meeting and socio-economic survey for sourcing primary data for analysis. The results indicate that where the swamp is vegetated by shrubs of different kinds, afforestation shows rapid success. And, where the swamp is dominated by grass species, afforestation success is slow. Terminalia ivorensis, Triplochiton scleroxylon and Ceiba pentandra registered quick impacts in height growth, stem development, canopy formation where the degraded land was originally covered with shrubs. Trees grow well when weed competition for essential resources is reduced through weed control. The study concludes that tree planting in swamp area is sustainable land management practice to redeem land degradation. Also, environmental benefits are imperatives but host communities derived near to zero social and economic benefits because such projects happen outside clean development mechanisms’ arrangement.